Physical Education and Sports Facilities and Infrastructure - Sahabuddin, Sahabuddin; Nawir, Nukrawi; Ishak, Muhammad (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
Facilities are all things tools and equipment used for physical education activities. Unfulfilled physical education facilities and activities in the physical education learning process will be disrupted and not run smoothly. Examples of physical education facilities such as balls (football, volleyball, basketball, baseball, etc.), beaters, rackets, and so on. Sports infrastructure is something that can facilitate and facilitate the course of the physical education learning process. Unfulfilled physical education infrastructure can hamper the effectiveness of physical education learning activities. Physical education infrastructure consists of courts (football, volleyball, basketball, handball, basketball, field tennis, badminton, softball, baseball, kipres, rounders, hockey, etc.), swimming pools, long jump tubs, stadiums, sports halls, and so on. The purpose of this study is to determine the existence, condition, and status of ownership of physical education facilities and infrastructure and motivation. Because physical education facilities and infrastructure support the achievement of physical education learning so that it runs effectively and efficiently. While motivation encourages someone to do something. A survey of physical education facilities and infrastructure in schools is a method or way to determine the number of existence, conditions and ownership status of physical education facilities and infrastructure in schools. This study aims to determine the condition of physical education facilities and infrastructure in schools. This research belongs to the type of survey research. The population of this study was SMK Negeri 2 Pangkep. The data analysis technique used is descriptive. Based on the results of data analysis, this study concluded that: (1) The percentage of fulfilment of the existence of physical education equipment following national education standards is 33%; (2) The percentage of fulfilment of the existence of physical education equipment following national education standards is 25%; and (3) The percentage of fulfilment of the existence of physical education facilities following national education standards is 33%.